Smart and affordable fuel grade analyzer design - Reme, Afsana Rahman; Islam, Md. Rawnak; Tanjim, Takia; Nazafi, Nafiz; Haque, K. M. Ekramul (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.